Optimum Government Size and Economic Growth in Indonesia: ARDL Model Approach - Khubbi Abdillah (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine the optimal government spending by analyzing the long-term and short-term relationship between government size and economic growth in Indonesia. The method used in this study is the ARDL model with secondary data from the World Development Indicators in 1966-2021. The results of the analysis show that initially government size has a significant positive effect on economic growth in the short run. But, in the long term, when the government size variable is in the form of a quadratic to determine a non-linear relationship, it shows a negative relationship to economic growth with a safe limit expenditure of 57.9% of national income. This study is in accordance with the Armey curve hypothesis. The policy recommendation in this study proposes that the government needs to control the amount of the budget so that its expenditure does not exceed the threshold.